2010
DOI: 10.1007/s00586-009-1247-7
|View full text |Cite
|
Sign up to set email alerts
|

The association of disproportionate skeletal growth and abnormal radius dimension ratio with curve severity in adolescent idiopathic scoliosis

Abstract: Abnormal anthropometric measurements during the peripubertal growth spurt have been documented in adolescent idiopathic scoliosis (AIS). Magnetic resonance (MR) imaging studies of the spine have suggested a disproportionate endochondral and membranous ossification in AIS. The present study aimed at investigating whether disproportional ossification and skeletal growth occurred in the peripheral bone of AIS patients using the radius as the target bone. Skeletally mature AIS girls with different severity (n = 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Furthermore, we have identified differences in function of adipose tissue as assessed by adipocyte-derived hormone levels at age 10 years, before the onset of clinically detectable scoliosis. Our results are consistent with the results of previous case-control studies, (11)(12)(13)(14)(15)(16)(17) but the effect size is smaller. Our findings suggest that the association between lower body weight and an increased risk of scoliosis is not due to bias and is explained by differences in both fat and lean mass.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we have identified differences in function of adipose tissue as assessed by adipocyte-derived hormone levels at age 10 years, before the onset of clinically detectable scoliosis. Our results are consistent with the results of previous case-control studies, (11)(12)(13)(14)(15)(16)(17) but the effect size is smaller. Our findings suggest that the association between lower body weight and an increased risk of scoliosis is not due to bias and is explained by differences in both fat and lean mass.…”
Section: Discussionsupporting
confidence: 92%
“…6 However, in the study of Qiu et al , 26 20% of circulation and enhance the leptin bioavailability in CSF. 37 , 44 Along with other studies, 6,9,10,14,16,45,46 AIS girls were found to have signifi cantly lower BMI and longer arm span than the healthy controls. This matches our observation on the change of sOB-R and FLI level in AIS girls.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies have indicated an association between estrogen receptor polymorphisms and scoliosis 19,20 , and another study indicated that girls with scoliosis had a tendency toward later menarche compared with girls who did not develop . Lower bone mineral density and disturbances in bone metabolism have also been related to AIS [33][34][35][36][37] ; the structural differences between males and females could contribute to the sex dimorphism of scoliosis. One study indicated that decreased differentiation ability of mesenchymal stem cells may contribute to osteopenia in individuals with AIS 38 .…”
Section: Discussionmentioning
confidence: 99%